1987
DOI: 10.1093/geronj/42.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction Benefits Learning and Motor Performance of Aged Mice

Abstract: Female C3B10RF1 mice maintained on either a control (approximately 95 kcal/week) or restricted (approximately 55 kcal/week) diet since weaning were tested in a behavioral battery at 11 to 15 or 31 to 35 months of age (middle-aged vs. aged). Age-related declines observed among control groups in tests of motor coordination (rotorod) and learning (complex maze) were prevented by the restriction regime. In addition, diet restriction increased locomotor activity in a runwheel cage among mice of both ages but did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
156
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(162 citation statements)
references
References 0 publications
5
156
1
Order By: Relevance
“…Average daily activity was higher for old male and female mice on CR when compared to controls (4,5). Rats as well as mice on CR and given access to a running wheel demonstrated higher levels of activity than controls (9,10,15). Everyother-day feeding differentially affected wheel running activity across the life span for male Wistar rats (9).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Average daily activity was higher for old male and female mice on CR when compared to controls (4,5). Rats as well as mice on CR and given access to a running wheel demonstrated higher levels of activity than controls (9,10,15). Everyother-day feeding differentially affected wheel running activity across the life span for male Wistar rats (9).…”
mentioning
confidence: 94%
“…As in the primate studies, activity is just one of many variables measured. Activity has been measured via wheel running, changes in locomotion, spontaneous activity, open field behavior, or load applied to a pressure transducer (6,19,13,15,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the effects of DR on motoric function, assessed both within and across tasks, gave evidence that DR had beneficial effects on motor systems. Previous studies have similarly reported beneficial effects of DR on age-related impairments in motor performance of rodents [6,35]. Second, cognitive function demonstrated prominent age-related performance deficits.…”
Section: Discussionmentioning
confidence: 69%
“…With regard to the central nervous system (CNS), recent studies have documented that a reduction of food intake in laboratory animals has beneficial effects on behavioural tests (8)(9)(10). DR attenuates the age-related loss of striatal dopamine receptors (11); suppresses age-related changes in dendritic spines (12); reduces the production of reactive oxygen species and it is able to counteract age-dependent changes in lipids of cortical membranes (13).…”
Section: Introductionmentioning
confidence: 99%